Perancangan dan Implementasi Sistem Smart Locker dengan Face Recognition Berbasis Internet of Things: Penerapan Teknologi Pengenal Wajah dalam Sistem Smart Locker - Ahmad, Rofiq; Agus, Agus; Junianto, Purbo Dwi (Politeknik Negeri Jakarta, 2024)
The Smart Locker System with Face Recognition is designed and developed to enhance security and efficiency in locker facility usage in environments requiring privacy and security, such as laboratories, institutions, or companies. The aim of this research is to create an innovative solution that combines facial recognition technology with an automated locking system to optimize locker access management. Facial recognition technology is used as the authentication method to unlock the locker door. The system integrates a camera on the ESP32-Cam to capture the user's face, which is then compared to a pre-registered facial database. If a match is detected, the locker door automatically opens. This Smart Locker System features four main functionalities: locker unlock, locker lock, face recognition, and image capturing. Testing results show that the Smart Locker System with Face Recognition successfully achieves adequate facial recognition accuracy and quick response times for opening and locking the locker door. The fastest time for the ESP32-Cam to recognize a face is 2.17 seconds. The quickest time to open the locker is 0.40 seconds, to close it is 0.41 seconds, and for image capture, 0.63 seconds.